Characteristics of Rare Inherited Retinal Dystrophies in Adaptive Optics—A Study on 53 Eyes - Katarzyna Samelska; Jacek Paweł Szaflik; Maria Guszkowska; Anna Katarzyna Kurowska; Anna Zaleska-Żmijewska (Diagnostics, 2023)
Inherited retinal dystrophies (IRDs) are genetic disorders that lead to the bilateral degeneration of the retina, causing irreversible vision loss. These conditions often manifest during the first and second decades of life, and their primary symptoms can be non-specific. Diagnostic processes encompass assessments of best-corrected visual acuity, fundoscopy, optical coherence tomography, fundus autofluorescence, fluorescein angiography, electrophysiological tests, and genetic testing. This study focuses on the application of adaptive optics (AO), a non-invasive retinal examination, for the assessment of patients with IRDs. AO facilitates the high-quality, detailed observation of retinal photoreceptor structures (cones and rods) and enables the quantitative analysis of parameters such as cone density (DM), cone spacing (SM), cone regularity (REG), and Voronoi analysis (<semantics>N%6</semantics>). AO examinations were conducted on eyes diagnosed with Stargardt disease (STGD, <semantics>N=36</semantics>), cone dystrophy (CD, <semantics>N=9</semantics>), and cone-rod dystrophy (CRD, <semantics>N=8</semantics>), and on healthy eyes (<semantics>N=14</semantics>). There were significant differences in the DM, SM, REG, and <semantics>N%6</semantics> parameters between the healthy and IRD-affected eyes (<semantics>p<0.001</semantics> for DM, SM, and REG; <semantics>p=0.008</semantics> for <semantics>N%6</semantics>). The mean DM in the CD, CRD, and STGD groups was 8900.39/mm<semantics>2</semantics>, 9296.32/mm<semantics>2</semantics>, and 16,209.66/mm<semantics>2</semantics>, respectively, with a significant inter-group difference (<semantics>p=0.006</semantics>). The mean SM in the CD, CRD, and STGD groups was 12.37 <semantics>μ</semantics>m, 14.82 <semantics>μ</semantics>m, and 9.65 <semantics>μ</semantics>m, respectively, with a significant difference observed between groups (<semantics>p=0.002</semantics>). However, no significant difference was found in REG and <semantics>N%6</semantics> among the CD, CRD, and STGD groups. Significant differences were found in SM and DM between CD and STGD (<semantics>p=0.014</semantics> for SM; <semantics>p=0.003</semantics> for DM) and between CRD and STGD (<semantics>p=0.027</semantics> for SM; <semantics>p=0.003</semantics> for DM). Our findings suggest that AO holds significant potential as an impactful diagnostic tool for IRDs.